Peningkatan Keuangan Keluarga Dalam Perspektif Maqashid Syari'ah (Studi Pada Driver Gojek dI Kota Palembang) - Abdullah Sahroni; Maftukhatusolikhah Maftukhatusolikhah (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Raden Fatah Palembang, Indonesia, 2020)
This research aims to discuss the increase in family income obtained by motorbike drivers in Palembang. The existence of a motorcycle taxi is one of the factors reducing the unemployment rate which will have an impact on increasing income and family welfare. Maqashid Shari'ah is used to see the impact of the phenomenon of increasing income on family welfare with five basic principles; hifz din, hifz nafs, hifz ‘aql, hifz mal and hifz nasab, with three levels of Daruriyyat, Hajiyyat and Tahsiniyyat. This research is a field research. This research is field research, the method used in this research was collaborative both qualitative and quantitative by distributed questionairre to respondents who became research's sample by some measurement cryterias with 5 assesment criteria and interview towards some informants to strenghten questionairre result. The technique of determining sample by using purposive sampling and analysis technique data questionairre by using quantitative descriptive and qualitative analysis with triangularltion approacment Magashid Suar'i. The result showed that there was an increasing income earned by the Gojek's drivers in Palembang city compare to other previous job before becoming a Gojek driver and also affecting family's prosperity